Nanowire Chemical/Biological Sensors: Status and a Roadmap for the Future. Issue 4 (11th December 2015) - Fennell, John F.; Liu, Sophie F.; Azzarelli, Joseph M.; Weis, Jonathan G.; Rochat, Sébastien; Mirica, Katherine A.; Ravnsbæk, Jens B.; Swager, Timothy M.
Abstract: Chemiresistive sensors are becoming increasingly important as they offer an inexpensive option to conventional analytical instrumentation, they can be readily integrated into electronic devices, and they have low power requirements. Nanowires (NWs) are a major theme in chemosensor development. High surface area, interwire junctions, and restricted conduction pathways give intrinsically high sensitivity and new mechanisms to transduce the binding or action of analytes. This Review details the status of NW chemosensors with selected examples from the literature. We begin by proposing a principle for understanding electrical transport and transduction mechanisms in NW sensors. Next, we offer the reader a review of device performance parameters. Then, we consider the different NW types followed by a summary of NW assembly and different device platform architectures. Subsequently, we discuss NW functionalization strategies. Finally, we propose future developments in NW sensing to address selectivity, sensor drift, sensitivity, response analysis, and emerging applications. Abstract : Down to the wire : Sensors based on chemiresistance can be readily integrated into electronic devices and are low priced compared to conventional analytical devides. This Review illustrates the advantages of such sensors, which transduce the binding or action of an analyte on a nanowire or nanowire arrangement into a signal.